2018
DOI: 10.1159/000487637
|View full text |Cite
|
Sign up to set email alerts
|

Higher Incidence Rates of Hypothyroidism and Late TSH Rise in Preterm Very-Low-Birth-Weight Infants at a Tertiary Care Center

Abstract: Background/Aims: Preterm newborns with a very low birth weight (VLBW) of < 1,500 g have an atypical form of hypothyroidism with a delayed rise in TSH, necessitating a second newborn screening specimen collection. The aims of this study were to survey the compliance with second newborn screening to detect delayed TSH rise in VLBW preterm infants at a tertiary care center, and to determine the rate of atypical hypothyroidism. Methods: Retrospective review of the records of 104 preterm VLBW infants. Late TSH rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Considering that 7(1.5%) in first one and1 (0.49%) in the second one, the level of TSH was more than20ng/dl, the probability of permanent hypothyroidism in our patients was low. In the research by Tfayli H, the rate of higher TSH level in preterm babies was significant and the researchers concluded that this result could be due to the use of povidone-iodine disinfectants in very low birth weight infants [18].…”
Section: Academic Journal Of Pediatrics and Neonatology Discussionmentioning
confidence: 99%
“…Considering that 7(1.5%) in first one and1 (0.49%) in the second one, the level of TSH was more than20ng/dl, the probability of permanent hypothyroidism in our patients was low. In the research by Tfayli H, the rate of higher TSH level in preterm babies was significant and the researchers concluded that this result could be due to the use of povidone-iodine disinfectants in very low birth weight infants [18].…”
Section: Academic Journal Of Pediatrics and Neonatology Discussionmentioning
confidence: 99%
“…[ 1 ] The frequency of congenital hypothyroidism is high in preterm and low-birth-weight (LBW) newborns compared to normal ones due to insufficient development of the hypothalamic-pituitary axis (1/400 vs 1/4000). [ 8 9 ]…”
Section: Introductionmentioning
confidence: 99%